A strain-inducing Ca 2+ Strain-inducing Ca 2+ Gradient-doped SrTiO3 photocatalyst materials, methods of making and use thereof

CN122974335APending Publication Date: 2026-10-27TONGJI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611370468.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-04
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

尽管上述改性手段已取得一定研究进展,但如何实现光生电荷从钛酸锶材料体相到表面的低损耗迁移,并在特定活性位点富集以完成氧化还原反应,仍是目前亟待突破的技术难题

Benefits of technology

[0016]根据本发明所涉及的应变诱导Ca2+梯度掺杂的SrTiO3光催化剂材料、制备方法及其应用,表明该SrTiO3光催化剂材料突破了传统均相掺杂工艺中改性维度单一、光生电荷复合率高的行业瓶颈,在单一SrTiO3钙钛矿体系内首次同步实现晶面工程、缺陷工程与应变工程的三重协同耦合。本制备方法依托Ca2+从颗粒内部向表面的定向自扩散行为,构建出从表面到体相连续递减的Ca2+浓度梯度,Ca2+的浓度梯度分布能够诱发晶格应变并构建极化电场,有效驱动体相光生电荷向材料表面快速迁移。同时,体系低缺陷态浓度可显著抑制光生电荷非辐射俘获损耗,提升表面有效光生电荷通量。此外,梯度分布的Ca2+可精准调控SrTiO3各向异性晶面的表面能,有助于调控材料各向异性晶面的暴露比例,使光生电荷定向输运至不同空间位点,实现还原与氧化活性位点的空间分离。基于此,本发明以制备的Ca0.04Sr0.96TiO3为典型代表,负载RhCrOx/CoOOH/助催化剂后,在100mW·cm-2的模拟太阳光照射条件下可稳定实现全解水反应,持续产出化学计量比的氢气与氧气,其在350±20 nm下的光催化全解水制氢表观量子产率(AQY)可达96.8%,太阳能制氢转化效率(STH)为1.08%。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122974335A_ABST
    Figure CN122974335A_ABST
Patent Text Reader

Abstract

The application provides a strain-induced Ca 2+ The application discloses a gradient-doped SrTiO3 photocatalyst material, a preparation method and application thereof, and belongs to the technical field of photocatalytic water decomposition materials. The SrTiO3 photocatalyst material breaks through the industry bottleneck of single modification dimension and high photo-generated charge recombination rate in a traditional homogeneous doping process, and for the first time realizes triple synergistic coupling of crystal face engineering, defect engineering and strain engineering in a single SrTiO3 perovskite system. 0.04 Sr 0.96 TiO3 as a typical representative, after loading RhCrO x / CoOOH / assistant catalyst, the stable full water splitting reaction can be realized under the irradiation condition of 100 mW·cm ‑2 The apparent quantum yield of the photocatalytic full water splitting for hydrogen production reaches 96.8% under the irradiation of 350±20 nm, and the solar hydrogen production conversion efficiency is 1.08%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of photocatalytic water splitting materials, specifically a strain-induced Ca... 2+ Gradient-doped SrTiO3 photocatalyst materials, preparation methods and applications. Background Technology

[0002] With global energy reserves dwindling and environmental degradation intensifying, there is an urgent need to develop sustainable energy solutions to replace fossil fuels. Photocatalytic water splitting technology is a promising green energy strategy that can achieve large-scale, low-cost green hydrogen production. The core bottleneck of this material system lies in the fact that traditional photocatalytic materials prepared by solid-state methods, hydrothermal methods, and molten salt methods generally suffer from insufficient surface photogenerated carrier flux, failing to efficiently supply the active charge required for water splitting, ultimately leading to low solar-to-hydrogen conversion efficiency. Therefore, constructing photocatalytic materials that combine low cost and high-efficiency charge separation performance is the key to promoting the practical application of photocatalytic water splitting technology.

[0003] Strontium titanate (SrTiO3), as a classic model photocatalytic material, serves as an important research platform for exploring performance enhancement mechanisms and uncovering the intrinsic principles of photocatalysis. Previous studies have confirmed that alumina (Al2O3) and aluminum trichloride (AlCl3) can act as surface morphology modifiers, precisely controlling the crystal structure of isotropic strontium titanate particles and modifying their morphology—characterized by a single exposed {100} crystal facet—to a structure where {110} and {111} crystal faces coexist in a specific ratio. Simultaneously, the introduction of Al... 3+ Harmful Ti in strontium titanate particles can be effectively suppressed through a charge compensation mechanism. 3+ Defect state generation. Other heterovalent dopant ions (Na) + K + Ga 3+ Similar modification effects have also been confirmed for other methods. Although the above modification methods have made some progress, how to achieve low-loss migration of photogenerated charges from the bulk phase to the surface of strontium titanate materials and enrich them at specific active sites to complete the redox reaction remains a technical challenge that urgently needs to be overcome. Summary of the Invention

[0004] This invention was made to solve the above-mentioned problems, and its purpose is to provide a strain-induced Ca 2+ Gradient-doped SrTiO3 photocatalyst materials, preparation methods and applications.

[0005] This invention provides a strain-induced Ca 2+A method for preparing gradient-doped SrTiO3 photocatalytic materials, characterized by comprising the following steps: Step S1, weighing calcium source, strontium source and titanium source according to a certain molar ratio, ball milling and mixing the three in ethanol solvent to obtain a uniformly dispersed suspension, drying the suspension and then subjecting it to high-temperature calcination to prepare a homogeneous calcium-strontium-titanium oxide precursor Ca with uniform component distribution and no gradient structure. x Sr 1-x TiO3, where 0≤x≤1.0; Step S2, the homogeneous calcium strontium titanium oxide precursor Ca x Sr 1-x TiO3 and molten salt system are mixed at a certain molar ratio and ground into powder. The powder is then subjected to a molten salt-mediated heteroion diffusion reaction at high temperature to obtain diffusion products. The diffusion products are washed and centrifuged multiple times to completely remove residual molten salt. After drying, Ca is obtained. 2+ A gradient-distributed SrTiO3 photocatalytic material with exposed anisotropic crystal planes; Step S3, the SrTiO3 photocatalytic material is dispersed in deionized water, and a certain amount of RhCrO is selectively loaded sequentially on the anisotropic crystal planes of the material using photodeposition. x With CoOOH, a strain-induced Ca2+-based compound was finally obtained. 2+ Gradient-doped SrTiO3 photocatalytic materials.

[0006] The present invention provides a strain-induced Ca-based method 2+ The preparation method of gradient-doped SrTiO3 photocatalytic material may also have the following characteristics: In step S1, the calcium source is calcium carbonate or calcium oxide, the strontium source is strontium carbonate or strontium oxide, and the titanium source is anatase titanium dioxide or rutile titanium dioxide. The purity of the calcium source, strontium source, and titanium source is not less than 99.9%, and the molar ratio of the calcium source, strontium source, and titanium source is (0.02~0.8):(0.2~0.98):1. In step S1, the ball milling speed is 300~600 r / min, the ball milling time is 2~6 h, the drying temperature is 40~90℃, the drying time is 8~24 h, and the calcination treatment is carried out in an aluminum-free high-temperature resistant container at a temperature of 950~1050℃ for 9~15 h.

[0007] The present invention provides a strain-induced Ca-based method 2+ The preparation method of gradient-doped SrTiO3 photocatalytic materials may also have the following characteristics: in step S2, the molten salt is strontium chloride hexahydrate or strontium nitrate, and the homogeneous calcium strontium titanium oxide precursor Ca x Sr 1-xThe molar ratio of TiO3 to molten salt system is 1:(10~100). The heating rate of the molten salt-mediated heteroion diffusion reaction is 3~6℃ / min, the temperature is 1050~1250℃, and the reaction time is 5~20h.

[0008] The present invention provides a strain-induced Ca-based method 2+ The preparation method of gradient-doped SrTiO3 photocatalytic material may also have the following characteristics: wherein, in step S3, RhCrO x The loading amounts of α-hydroxyl group (α-hydroxyl group) are 0.01–5 wt%, and the loading amounts of CoOOH are 0.01–4 wt%. RhCrO x The mass ratio of Rh to Cr in RhCrO is controlled at (2 ~ 3):1. x The rhodium source in RhCrO is rhodium trichloride or rhodium acetylacetonate. x The chromium source in CoOOH is chromium nitrate or potassium chromate, and the cobalt source in CoOOH is cobalt nitrate or cobalt acetate.

[0009] The present invention provides a strain-induced Ca-based method 2+ The preparation method of gradient-doped SrTiO3 photocatalytic materials can also have the following characteristics: in step S2, by controlling the temperature and time of the molten salt-mediated heteroion diffusion reaction, the Ca2+ content can be precisely controlled. 2+ From homogeneous calcium strontium titanium oxide precursor Ca x Sr 1-x The diffusion depth from the interior of TiO3 to the particle surface can be precisely adjusted within the range of 20~500 nm to achieve gradient layer thickness.

[0010] The present invention provides a strain-induced Ca-based method 2+ The preparation method of gradient-doped SrTiO3 photocatalytic material may also have the following characteristics: in step S2, the exposed crystal planes of the SrTiO3 photocatalytic material are mainly {100} and {110}, and the Ca is controlled. 2+ The content of the introduced {100} / {110} crystal plane ratio can be adjusted between 0.3 and 1.2.

[0011] The present invention provides a strain-induced Ca-based method 2+ The preparation method of gradient-doped SrTiO3 photocatalytic material may also have the following characteristics: in step S2, the atomic ratio of Ca element on the particle surface of SrTiO3 photocatalytic material is 1.5 to 4 times that of Ca element in bulk phase, and the defect state density of SrTiO3 photocatalytic material is less than 50% of that of undoped SrTiO3.

[0012] The present invention provides a strain-induced Ca-based method2+ The preparation method of gradient-doped SrTiO3 photocatalytic material may also have the following characteristics: wherein, in step S2, Ca 2+ The gradient distribution induces gradient strain in the SrTiO3 lattice, with the lattice strain value gradually decreasing from 1% to 3% on the surface to below 0.5% in the bulk phase. This gradient lattice strain constructs a directional polarized electric field inside the material, which drives the directional migration of photogenerated charges in the bulk phase to the material surface.

[0013] The present invention also provides a strain-induced Ca-based method. 2+ Gradient-doped SrTiO3 photocatalysts possess the following characteristics: through the aforementioned strain-induced Ca... 2+ Gradient-doped SrTiO3 photocatalytic materials were prepared using a specific method.

[0014] This invention also provides a strain-induced Ca 2+ Applications of gradient-doped SrTiO3 photocatalytic materials.

[0015] The role and effect of invention

[0016] The strain-induced Ca involved in the present invention 2+ The graded-doped SrTiO3 photocatalyst material, its preparation method, and its application demonstrate that this SrTiO3 photocatalyst material overcomes the industry bottlenecks of single modification dimension and high photogenerated charge recombination rate in traditional homogeneous doping processes. For the first time, it simultaneously achieves the triple synergistic coupling of crystal plane engineering, defect engineering, and strain engineering within a single SrTiO3 perovskite system. This preparation method relies on Ca... 2+ The directional self-diffusion behavior from the particle interior to the surface constructs a Ca concentration that continuously decreases from the surface to the bulk phase. 2+ Concentration gradient, Ca 2+ The concentration gradient distribution of Ca can induce lattice strain and construct a polarization electric field, effectively driving the rapid migration of bulk photogenerated charges to the material surface. Simultaneously, the low defect state concentration of the system can significantly suppress non-radiative trapping losses of photogenerated charges, increasing the effective photogenerated charge flux on the surface. Furthermore, the gradient distribution of Ca... 2+ The surface energy of the anisotropic crystal planes of SrTiO3 can be precisely controlled, which helps to regulate the exposure ratio of the anisotropic crystal planes in the material, enabling the directional transport of photogenerated charges to different spatial sites and achieving spatial separation of reduction and oxidation active sites. Based on this, the present invention uses the prepared Ca 0.04 Sr 0.96 TiO3 is a typical example, supported on RhCrO x After using / CoOOH / as a co-catalyst, at 100 mW·cm -2Under simulated sunlight irradiation conditions, it can stably achieve the whole water splitting reaction and continuously produce stoichiometric amounts of hydrogen and oxygen. Its apparent quantum yield (AQY) for photocatalytic whole water splitting to produce hydrogen at 350±20 nm can reach 96.8%, and its solar hydrogen production conversion efficiency (STH) is 1.08%. Attached Figure Description

[0017] Figure 1 These are the X-ray powder diffraction patterns of Examples 1-10 of the present invention;

[0018] Figure 2 This is a graph showing the variation of cell parameters with Ca content in Examples 1-10 of the present invention;

[0019] Figure 3 Sr in Embodiment 2 of the present invention + Ca + and Ti + Time-of-flight secondary ion mass spectra;

[0020] Figure 4 This is an example of spherical aberration electron microscopy and geometric phase stress analysis of the surface region in Embodiment 2 of the present invention;

[0021] Figure 5 This is an example of spherical aberration electron microscopy and geometric phase stress analysis of the bulk region in Embodiment 2 of the present invention;

[0022] Figure 6 This is a scanning electron microscope image of Example 2 of the present invention without the deposited co-catalyst;

[0023] Figure 7 In Embodiment 2 of the present invention, Ca 2+ Comparison of the effect of gradient distribution on the reduction of surface energy of SrTiO3 {100}, {111} and {110} crystal planes;

[0024] Figure 8 This is a linear scan surface photovoltage spectrum along the {100} and {110} crystal planes of Embodiment 2 of the present invention;

[0025] Figure 9 This is Example 2 of the present invention, which involves the photodeposition of RhCrO. x Scanning electron microscope image after adding CoOOH co-catalyst;

[0026] Figure 10 This is a scanning electron microscope image of Example 9 of the present invention without the deposited co-catalyst;

[0027] Figure 11 These are scanning electron microscope images of RhCrOx and CoOOH cocatalysts after photodeposition in Example 9 of this invention;

[0028] Figure 12These are the electron paramagnetic resonance spectra of Embodiments 2 and 9 of the present invention;

[0029] Figure 13 These are the surface photovoltage spectra of Embodiments 2 and 9 of the present invention;

[0030] Figure 14 Examples 1-10 of this invention are based on simulated sunlight (100mW·cm²). -2 Performance diagram of photocatalytic water splitting for hydrogen and oxygen production under irradiation; and

[0031] Figure 15 This is Example 2 of the present invention, under simulated sunlight (100mW·cm). -2 Photocatalytic water splitting for hydrogen and oxygen production cycle performance under irradiation. Detailed Implementation

[0032] To make the technical means, creative features, achieved objectives and effects of this invention easier to understand, the following embodiments, in conjunction with the accompanying drawings, illustrate a strain-induced Ca... 2+ The preparation method and application of gradient-doped SrTiO3 photocatalytic materials are described in detail.

[0033] Example 1

[0034] This embodiment 1 provides a strain-induced Ca... 2+ Gradient-doped SrTiO3 photocatalytic materials and their preparation methods, specifically including the following steps:

[0035] Step S1: Weigh out calcium source Ca2CO3, strontium source SrCO3, and titanium source anatase TiO2 in a ratio of 0.02:0.98:1. Ball mill the mixture in ethanol to obtain a uniformly dispersed suspension. Dry the suspension at 40°C for 24 hours, then transfer it to an Al-free crucible and calcine at 1000°C for 10 hours. After the reaction is complete, allow it to cool naturally to room temperature to obtain a homogeneous precursor CaO2 with uniform component distribution and no gradient structure. 0.02 Sr 0.98 TiO3.

[0036] Step S2: The homogeneous precursor Ca obtained in step S1 0.02 Sr 0.98 TiO3 and strontium chloride hexahydrate were mixed and ground thoroughly at a ratio of 1:100 for 45 min to obtain a homogeneous powder. The powder was then transferred to a lidded crucible free of Al for molten salt-mediated heteroion diffusion reaction. After natural cooling, the diffusion product was collected, repeatedly washed, and centrifuged to obtain a final product free of molten salt. The final product was dried to obtain a product containing Ca. 2+ Gradient-distributed Ca, simultaneously exposing anisotropic crystal planes0.02 Sr 0.98 TiO3 photocatalytic material.

[0037] Step S3: First weigh a certain amount of Ca 2+ Gradient-distributed Ca, simultaneously exposing anisotropic crystal planes 0.02 Sr 0.98 TiO3 is mixed with an aqueous solution of rhodium trichloride, and the amount of rhodium trichloride is controlled so that the mass ratio of rhodium to Ca is such that... 0.02 Sr 0.98 0.1 wt% TiO3 was added. The mixture was stirred to form a solution, which was then photodeposited under full-spectrum xenon lamp irradiation for 1 hour to obtain Rh / Ca. 0.02 Sr 0.98 TiO3. Then add a certain amount of potassium chromate aqueous solution, controlling the amount of potassium chromate so that the mass ratio of chromium to Ca is [missing information]. 0.02 Sr 0.98 0.05 wt% TiO3 was added. The mixture was stirred to form a solution, which was then photodeposited under full-spectrum xenon lamp irradiation for 0.5 h to obtain RhCrO2. x / Ca 0.02 Sr 0.98 TiO3.

[0038] Weigh a certain amount of RhCrO x / Ca 0.02 Sr 0.98 TiO3 is mixed with an aqueous solution of cobalt nitrate, and the amount of cobalt nitrate is controlled so that the mass ratio of cobalt to Ca is such that the mass ratio of cobalt to Ca is [missing information]. 0.02 Sr 0.98 0.05 wt% TiO3 was added. The mixture was stirred to form a solution, which was then photodeposited under full-spectrum xenon lamp irradiation for 0.5 h to obtain RhCrO2. x / CoOOH / Ca 0.02 Sr 0.98 TiO3. The mixture after photodeposition was collected by centrifugation at 9000 rpm for 10 min. The collected precipitate was then dried in a 40℃ drying oven for 24 h to obtain RhCrO3. x / CoOOH / Ca 0.02 Sr 0.98 TiO3 powder.

[0039] Based on Example 1 above, different examples can be obtained by changing the molar ratio of calcium source, strontium source, and titanium source. Except for the different molar ratios of calcium source, strontium source, and titanium source, all other reaction parameters are the same. The molar ratios of calcium source, strontium source, and titanium source for Examples 1 to 10 are shown in Table 1:

[0040] Table 1. Molar ratios of calcium, strontium, and titanium sources in Examples 1-10

[0041] 1 0.02:0.98:1 2 0.04:0.96:1 3 0.06:0.94:1 4 0.08:0.92:1 5 0.2:0.8:1 6 0.4:0.6:1 7 0.6:0.4:1 8 0.8:0.2:1 9 0:1:1 10 1:0:1

[0042] Figure 1 These are the X-ray powder diffraction patterns of Examples 1-10 of the present invention. Figure 2 This is a graph showing the variation of cell parameters with Ca content in Examples 1-10 of the present invention. Figure 3 Sr in Embodiment 2 of the present invention + Ca + and Ti + The time-of-flight secondary ion mass spectrum. Figure 4 This is a spherical aberration electron microscope and geometric phase stress analysis of the surface region in Embodiment 2 of the present invention. Figure 5 This is a spherical aberration electron microscope and geometric phase stress analysis of the bulk region in Embodiment 2 of the present invention. Figure 6 This is a scanning electron microscope image of Example 2 of the present invention without the deposition of the co-catalyst. Figure 7 In Embodiment 2 of the present invention, Ca 2+ Comparison of the reduction in surface energy of SrTiO3 {100}, {111} and {110} crystal planes by gradient distribution. Figure 8 This is a linear scan surface photovoltage spectrum along the {100} and {110} crystal planes of Embodiment 2 of the present invention. Figure 9 This is Example 2 of the present invention, which involves the photodeposition of RhCrO. x Scanning electron microscope image after adding CoOOH cocatalyst. Figure 10 This is a scanning electron microscope image of Example 9 of the present invention without the deposition of the co-catalyst. Figure 11 This is Example 9 of the present invention, which involves the photodeposition of RhCrO. x Scanning electron microscope image after adding CoOOH cocatalyst. Figure 12 These are the electron paramagnetic resonance spectra of Embodiments 2 and 9 of the present invention. Figure 13 These are surface photovoltage spectra of Embodiments 2 and 9 of the present invention. Figure 14 Examples 1-10 of this invention are based on simulated sunlight (100mW·cm²). -2 Photocatalytic water splitting for hydrogen and oxygen production under irradiation. Figure 15 This is Example 2 of the present invention, under simulated sunlight (100mW·cm). -2 Photocatalytic water splitting for hydrogen and oxygen production cycle performance under irradiation.

[0043] like Figure 1As shown, X-ray diffraction analysis revealed that the diffraction patterns of both the calcium-doped strontium titanate samples and the undoped strontium titanate samples prepared in Examples 1-10 matched the standard card (JCPDS: 00-005-0634), proving that no crystal structure phase transition occurred in the material before and after calcium doping, and no impurity phases were generated. The systematic shift of the diffraction peaks to higher angles with increasing calcium content confirms that the calcium doping process... 2+ Doping can form a complete series of solid solutions of Ca x Sr 1-x TiO3 (0≤x≤1). This further demonstrates that the doped system has good compositional tunability and can construct a controllable calcium concentration gradient within the strontium titanate matrix.

[0044] like Figure 2 As shown, the XRD refinement results of Examples 1-10 indicate that with a smaller Ca... 2+ Cation substitution of Sr 2+ This induces shrinkage in perovskite unit cells, and this doping-dependent change exhibits an approximately linear trend, thus allowing for the modulation of Ca... 2+ Concentration allows for continuous adjustment of the crystal structure between cubic and orthorhombic phases. For Ca in Examples 2-9... 2+ Gradient doping of SrTiO3 particles induces internal strain due to the resulting non-uniform lattice shrinkage, the magnitude of which is positively correlated with the local shrinkage rate.

[0045] like Figure 3 As shown, the quantitative statistical analysis results of time-of-flight secondary ion mass spectrometry further confirm that with the extension of sputtering etching time, Ca... 2+ In gradient-doped SrTiO3, the Ca+ signal intensity gradually decreases and eventually stabilizes. This indicates that Ca... 2+ The calcium content in the near-surface region of gradient-doped SrTiO3 particles decreases sharply from the outside to the inside, with only trace amounts of calcium remaining in the bulk phase. This is the Ca2+ obtained by this invention. 2+ Gradient-doped SrTiO3 photocatalytic materials.

[0046] like Figure 4 and Figure 5 As shown, Ca 2+ The interplanar spacing of the {100} crystal planes on the surface of the gradient-doped SrTiO3 particles is 3.86 Å, significantly smaller than the 3.94 Å measured in the bulk region, corresponding to a lattice shrinkage exceeding 2%. Furthermore, geometric phase analysis (GPA) was performed to quantify local strain. Strain tensor analysis in the horizontal direction shows that Ca... 2+ Significant tensile strain exists on the surface region of gradient-doped SrTiO3 particles, while the bulk region exhibits almost no strain. This strain distribution is consistent with... Figure 2 The Ca shown 2+ The gradient concentration distributions match well.

[0047] like Figure 6 As shown, a small amount of Ca is introduced. 2+ Subsequently, {110} and {111} crystal planes appeared at the truncated edges and corners of the SrTiO3 particles, indicating a gradient distribution of Ca. 2+ It helps to regulate the exposure of anisotropic crystal planes in SrTiO3 materials.

[0048] like Figure 7 As shown, density functional theory calculations indicate that Ca 2+ Gradient doping exhibits a facet-dependent response. In pristine SrTiO3, the {100} facet has the lowest surface energy and is thermodynamically the most stable, thus being easier to form than the {110} and {111} facets. When Ca... 2+ When introduced into surface or subsurface sites by gradients, the surface energy decreases significantly more for the {110} and {111} crystal planes than for the {100} crystal plane. This relative change in surface energy between different crystal planes is expected to kinetically modulate the growth path of SrTiO3, thereby affecting the morphology of SrTiO3 particles.

[0049] like Figure 8 As shown, Ca was examined using a Kelvin probe force microscope. 2+ The surface charge distribution of gradient-doped SrTiO3 particles was characterized. Spatially resolved surface photovoltage images showed a uniform positive signal, indicating that photoexcited holes accumulate on the surface. Furthermore, the surface photovoltage signal of the {110} crystal plane was 43.2 mV higher than that of the {100} crystal plane, directly proving the spatial separation of photoexcited electrons and holes.

[0050] like Figure 9 As shown, RhCrO x Particles selectively deposit on Ca 2+ The gradient-doped SrTiO3 particles are located on the {100} crystal plane, while CoOOH flocculents form on the {110} and {111} crystal planes. This result confirms the crystal plane-determined charge distribution, i.e., photoexcited electrons are enriched on the {100} crystal plane, while holes are enriched on the {110} and {111} crystal planes. Based on this directional charge flow, the hydrogen evolution co-catalyst RhCrO x And oxygen evolution co-catalyst CoOOH in Ca 2+ The gradient-doped SrTiO3 particles are spatially separated on the surface.

[0051] like Figure 10 As shown, the undoped SrTiO3 particles are cubic in shape, with their surfaces surrounded by isotropic {100} crystal planes and no anisotropic crystal planes exposed.

[0052] like Figure 11As shown, RhCrO photodeposited on the surface of undoped SrTiO3 particles x The CoOOH cocatalyst is randomly distributed and has no crystal facet selectivity.

[0053] like Figure 12 As shown, the electron paramagnetic resonance (EPR) spectra provide direct evidence of the defect types and concentrations in Examples 2 and 9. Signals were detected at g = 2.001, g = 1.997, and g = 1.929, corresponding to oxygen vacancies, bulk Ti, and other defects, respectively. 3+ and surface Ti 3+ Species. Compared to undoped SrTiO3, in Ca 2+ The significant decrease in these signal intensities in gradient-doped SrTiO3 indicates that Ca... 2+ Gradient-doped SrTiO3 materials have a low defect density.

[0054] like Figure 13 As shown, Ca 2+ The surface photovoltage signal intensity of gradient-doped SrTiO3 is significantly higher than that of undoped SrTiO3. It is worth noting that Ca... 2+ After gradient doping, the surface photovoltage signal intensity increased significantly from 0.017 mV to 1.38 mV, an increase of approximately 80 times. This indicates that the introduction of Ca... 2+ Gradient doping can effectively suppress surface defect states of SrTiO3 particles, thereby reducing harmful photogenerated charge recombination.

[0055] like Figure 14 As shown, under simulated sunlight (100 mW·cm²), -2 Under irradiation, Ca in Examples 1-9 2+ Gradient-doped SrTiO3 particles exhibited significantly enhanced photocatalytic water splitting activity. Among them, Example 2 showed the highest photocatalytic water splitting activity, which was about 3.5 times that of the undoped SrTiO3 in Example 9. Its apparent quantum yield (AQY) for photocatalytic water splitting to produce hydrogen at 350±20 nm reached 96.8%, and its solar hydrogen conversion efficiency (STH) was 1.08%.

[0056] like Figure 15 As shown, the performance of Ca in Example 2 was evaluated through repeated test cycles. 2+ Durability of photocatalytic water splitting reaction of gradient-doped SrTiO3 particles. No significant decrease in activity was observed over four consecutive test cycles, indicating excellent operational stability.

[0057] Those skilled in the art should understand that this invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to this invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the invention as claimed. The scope of protection of this invention is defined by the appended claims and their equivalents.

Claims

1. A strain-induced Ca 2+ A method for preparing gradient-doped SrTiO3 photocatalytic materials, characterized in that, Includes the following steps: Step S1: Weigh calcium source, strontium source, and titanium source according to a certain molar ratio, and ball-mill them together in ethanol solvent to obtain a uniformly dispersed suspension. After drying the suspension, perform high-temperature calcination to prepare a homogeneous calcium-strontium-titanium oxide precursor Ca with uniform component distribution and no gradient structure. x Sr 1-x TiO3, where 0 ≤ x ≤ 1.0; Step S2, the homogeneous calcium strontium titanium oxide precursor Ca x Sr 1-x TiO3 and a molten salt system are mixed at a specific molar ratio and ground into powder. The powder is then subjected to a molten salt-mediated heteroion diffusion reaction to obtain a diffusion product. This diffusion product is repeatedly washed and centrifuged to completely remove residual molten salt. After drying, Ca is obtained. 2+ SrTiO3 photocatalytic material with gradient distribution and exposed anisotropic crystal planes; Step S3: The SrTiO3 photocatalytic material is dispersed in deionized water, and a certain amount of RhCrO is selectively loaded sequentially on the anisotropic crystal surfaces of the material using photodeposition. x With CoOOH, a strain-induced Ca2+-based compound was finally obtained. 2+ Gradient-doped SrTiO3 photocatalytic materials.

2. A strain-induced Ca method according to claim 1 2+ A method for preparing gradient-doped SrTiO3 photocatalytic materials, characterized by: in, In step S1, the calcium source is calcium carbonate or calcium oxide, the strontium source is strontium carbonate or strontium oxide, and the titanium source is anatase titanium dioxide or rutile titanium dioxide. The purity of the calcium source, strontium source, and titanium source is not less than 99.9%, and the molar ratio of the calcium source, strontium source, and titanium source is x:(1-x):

1. The ball milling mixing speed is 300~600 r / min, and the time is 2~6 h. The drying temperature is 40~90℃, and the drying time is 8~24h. The calcination process is carried out in a high-temperature resistant container without aluminum, at a temperature of 950~1050℃, for a time of 9~15h.

3. A strain-induced Ca method according to claim 1 2+ A method for preparing gradient-doped SrTiO3 photocatalytic materials, characterized by: in, In step S2, the molten salt is strontium chloride hexahydrate or strontium nitrate, and the homogeneous calcium strontium titanium oxide precursor Ca x Sr 1-x The molar ratio of TiO3 to the molten salt system is 1:(10~100). The heating rate of the molten salt-mediated heteroion diffusion reaction is 3~6℃ / min, the temperature is 1050~1250℃, and the reaction time is 5~20 hours.

4. A strain-induced Ca method according to claim 1 2+ A method for preparing gradient-doped SrTiO3 photocatalytic materials, characterized by: in, In step S3, the RhCrO x The loading amount of the substance is 0.01–5 wt%, the loading amount of the CoOOH is 0.01–4 wt%, and the loading amount of the RhCrO is 0.01–5 wt%. x The mass ratio of Rh to Cr elements in the solution is controlled at (2~3):

1. The RhCrO x The rhodium source in the RhCrO is rhodium trichloride or rhodium acetylacetonate, and the RhCrO x The chromium source in the CoOOH is chromium nitrate or potassium chromate, and the cobalt source in the CoOOH is cobalt nitrate or cobalt acetate.

5. A strain-induced Ca method according to claim 1 2+ A method for preparing gradient-doped SrTiO3 photocatalytic materials, characterized by: in, In step S2, the temperature and time of the molten salt-mediated heteroion diffusion reaction are precisely controlled to regulate Ca. 2+ From the homogeneous calcium strontium titanium oxide precursor Ca x Sr 1-x The diffusion depth from the interior of TiO3 to the particle surface is increased, thereby enabling precise adjustment of the gradient layer thickness within the range of 20~500nm.

6. A strain-induced Ca method according to claim 1 2+ A method for preparing gradient-doped SrTiO3 photocatalytic materials, characterized by: in, In step S2, the exposed crystal planes of the SrTiO3 photocatalyst material are mainly {100} and {110}, and the Ca is controlled to... 2 + The content of the introduced {100} / {110} crystal plane ratio can be adjusted between 0.3 and 1.

2.

7. A strain-induced Ca method according to claim 1 2+ A method for preparing gradient-doped SrTiO3 photocatalytic materials, characterized by: in, In step S2, the atomic ratio of Ca on the particle surface of the SrTiO3 photocatalytic material is 1.5 to 4 times that of the bulk Ca atomic ratio, and the defect state density of the SrTiO3 photocatalytic material is less than 50% of that of undoped SrTiO3.

8. A strain-induced Ca method according to claim 1 2+ A method for preparing gradient-doped SrTiO3 photocatalytic materials, characterized by: in, In step S2, the Ca 2+ The gradient distribution induces gradient strain in the SrTiO3 lattice, with the lattice strain value gradually decreasing from 1% to 3% on the surface to below 0.5% in the bulk phase. This gradient lattice strain constructs a directional polarized electric field inside the material, which drives the directional migration of photogenerated charges in the bulk phase to the material surface.

9. A method based on strain-induced Ca 2+ Gradient-doped SrTiO3 photocatalytic materials are characterized by, Using any one of claims 1 to 8, a strain-induced Ca 2+ The gradient-doped SrTiO3 photocatalytic material was prepared by a specific method.

10. A strain-induced Ca method as described in claim 9 2+ Preparation method and application of gradient-doped SrTiO3 photocatalytic materials.